Sustainable Tourism Development in Jordan. Measuring Customer Satisfaction of American Tourists Visiting Petra and Mount Nebo in Jordan - ROUSAN, Ramzi AL; IBRAHEIM, Hussien; BADER, Malek; KHASAWNEH, Nermin (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020DO - 10.14505//jemt.v11.4(44).26, 2020)
This study investigates the effect of selected factors on the choice of tourist sites in Jordan. These selected factors form the basis for the satisfaction level of American tourist visiting Petra and Mount Nebo. The selected factors are chosen based on the perception of quality of services by American tourists who are focused on three main factors of “destination services” related to “accommodation, facilities at destination and the travel agency”. The opinions and feedbacks of the tourist guides were analysed to provide more insight into the satisfaction level of the American tourist. Specific questionnaires were distributed among American tourists via 10 travel agencies to gather data. Besides, all the tourist guides who supported this study were interviewed for cross-checking purposes. The findings suggested the Americans were generally satisfied with their vacation to Petra and Mount Nebo except for cleanliness at the nearby towns and the sites. This paper seeks to provide data on the satisfaction level of American tourists and the factors that need to be prioritized to enhance higher level of customer satisfaction. This will further improve the destination services for a particular tourist site. Besides, stakeholders need to further improve their tourism aspects to enhance tourist satisfaction.